Under workload but not alone: The power of organizational support in employee performance - Wardoyo, Sudibyo; Sausi, Fauji; Kambara, Roni (Social Sciences Insights Journal, 2025)
This paper investigates the effect of workload on employee performance and the moderating role of perceived organizational support (POS) in a high-pressure public sector setting, specifically within a regional police department in Indonesia. A quantitative approach was adopted using a census survey of 106 police personnel, employing validated questionnaires to measure workload, POS, and performance. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.1. Results show that workload had a negative but statistically insignificant effect on employee performance, and POS did not significantly moderate this relationship. However, POS had a strong positive direct effect on performance, indicating its value as an independent factor in enhancing outcomes. These findings highlight the importance of genuine organizational support in maintaining performance, especially in the public sector. This study adds to the literature by demonstrating the limited moderating effect of POS under high-pressure conditions, while emphasizing the strategic role of direct support mechanisms to sustain employee performance in public institutions.